Lactiplantibacillus plantarum ST-III and Lacticaseibacillus rhamnosus KF7 Enhance the Intestinal Epithelial Barrier in a Dual-Environment In Vitro Co-Culture Model - Yilin Zhang; Rachel C. Anderson; Chunping You; Ajitpal Purba; Minghui Yan; Paul Maclean; Zhenmin Liu; Dulantha Ulluwishewa (Microorganisms, 2024)
Intestinal barrier hyperpermeability, which is characterised by impaired tight junction proteins, is associated with a variety of gastrointestinal and systemic diseases. Therefore, maintaining intestinal barrier integrity is considered one of the effective strategies to reduce the risk of such disorders. This study aims to investigate the potential benefits of two probiotic strains (Lactiplantibacillus plantarum ST-III and Lacticaseibacillus rhamnosus KF7) on intestinal barrier function by using a physiologically relevant in vitro model of the intestinal epithelium. Our results demonstrate that both strains increased transepithelial electrical resistance, a measure of intestinal barrier integrity. Immunolocalisation studies indicated that this improvement in barrier function was not due to changes in the co-localisation of the tight junction (TJ) proteins ZO-1 and occludin. However, we observed several modifications in TJ-related genes in response to the probiotics, including the upregulation of transmembrane and cytosolic TJ proteins, as well as TJ signalling proteins. Gene expression modulation was strain- and time-dependent, with a greater number of differentially expressed genes and higher fold-change being observed in the L. plantarum ST-III group and at the latter timepoint. Further studies to investigate how the observed gene expression changes can lead to enhanced barrier function will aid in the development of probiotic foods to help improve intestinal barrier function.